The Effect of Financial Knowledge, Time Saving, Money Saving, and Convenience to Use Intention Digital Mobile Payment Apps in Bekasi City - Christophorus Indra Wahyu Putra; Dodi Kurniawan (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study was used to The Effect of Financial Knowledge, Time Saving, Money Saving, and Convenience in using Intention Digital Mobile Payment Apps in Bekasi City. This research is quantitative research where the object used is an employee in a user digital mobile payment app in Bekasi city. This research was conducted using a non-probability sampling technique with a purposive sampling method. The number of samples used in this study was 96 respondents. The design used in this study is hypothesis testing using a structural equitation model (SEM) – SmartPLS 3.0. The results of this study provide an explanation that the financial knowledge variable affects the use intention digital mobile payment, time saving affects se intention of digital mobile payment, money-saving affects the use intention of digital mobile payment, and convenience affects use intention of digital mobile payment. This research has a limited object of research which is only conducted on user digital mobile payment in Bekasi city. This is used as a suggestion for future researchers.